Patient and Tissue Identification in the Assisted Reproductive Technology Laboratory - Pomeroy, Kimball O.; Racowsky, Catherine (Seminars in Reproductive Medicine, 2012)
Several high-profile cases involving in vitro fertilization have recently received considerable media attention and highlight the importance of assuring patient and tissue identification. Within the assisted reproductive technology (ART) laboratory, there are many steps where wrong patient or tissue identity could have drastic results. Erroneous identity can result in tragic consequences for the patient, the laboratory, and for those working in the program as a whole. Such errors can result in enormous psychological and financial costs, as well as a loss in confidence. There are several critical steps that should be taken every single time and for each specific procedure performed in the ART laboratory to ensure the correct identification of patients and their tissue. These steps should be detailed in protocols that include the method of identification, the two unique identifiers that will be used, the sources of these identifiers, and often a system in which more than one person is involved in the identification. Each protocol should ideally include a checklist that is actively used for the implementation of each procedure. The protocol should also indicate what to do if the identification does not match up, including rapid handling and notification of the patient involved in the error. All ART laboratories should instill in their employees an atmosphere of full and open disclosure for cases where mistakes are made.
Keywords: ART laboratory; safety; patient; tissue; identification; protocols; checklists